Description of a new species of the genus Caeneressa from China, with a checklist of the genus (Lepidoptera: Erebidae) - Davlatov, Abdulaziz M.; Wu, Chun-Sheng (Zootaxa, 2018)
A new species, Caeneressa fangae C.-S. Wu, is described from Sichuan, China. Image of adult and genitalia of the new species is provided. Caeneressa serrata (Hampson) is excluded from the fauna of China. A checklist of the species and subspecies of the genus Caeneressa is given on a worldwide basis.